Working memory related brain network connectivity in individuals with schizophrenia and their siblings - Repovs, Grega; Barch, Deanna M. (Frontiers in Human Neuroscience, 2012)
A growing number of studies have reported altered functional connectivity in schizophrenia during putatively “task-free” states and during the performance of cognitive tasks. However, there have been few systematic examinations of functional connectivity in schizophrenia across rest and different task states to assess the degree to which altered functional connectivity reflects a stable characteristic or whether connectivity changes vary as a function of task demands. We assessed functional connectivity during rest and during thee working memory loads of an N-back task (0-back, 1-back, 2-back) among: 1) individuals with schizophrenia (N=19); the siblings of individuals with schizophrenia (N=28); 3) healthy controls (N=10) and the siblings of healthy controls (n=17). We examined connectivity within and between four brain networks: 1) frontal-parietal (FP); 2) cingulo-opercular (CO); 3) cerebellar (CER); and 4) default mode (DMN). We found that connectivity within the DMN and FP increased significantly between resting state and 0-back, while connectivity within the CO and CER decreased significantly between resting state and 0-back. Further, the DMN became significantly more “anti-correlated” with the FP, CO and CER networks during 0-back as compared to rest. Additionally, we found that connectivity within both the DMN and FP was further modulated by memory load, and that connectivity between the FP and both CO and CER networks increased with memory load. Individuals with schizophrenia and their siblings showed consistent reductions in connectivity between both the FP and CO networks with the CER network, a finding that was similar in magnitude across rest and all levels of working memory load. These findings are consistent with the hypothesis that altered functional connectivity in schizophrenia reflects a stable characteristic that is present across cognitive states.